Data stories: speculative methods for researching digital surveillance in higher education - Ross, Jen; Wilson, Anna (Proceedings of the International Conference on Networked Learning, 2024)
Higher education systems have always involved monitoring through data collection, assessment, and evaluation, shaping the intellectual work, and tracking the bodies and activities of students and teachers. However, surveillance in many higher education settings has become increasingly pervasive and fine-grained as monitoring and data-gathering technologies grow in sophistication and as the quantification and measurement of everything from outcomes to student satisfaction to engagement is increasingly valued in universities. Concerns are growing about negative impacts on learning relationships, exploitative commercial uses of collected student data, discriminatory practices, and even political, social, or physical harm inflicted because of surveillance and monitoring. At the same time, the complex surveillance cultures of higher education make it difficult to disentangle personal and collective responsibility, understand the gap between intentions and impacts, or navigate the significant risks that can come, for some, with speaking about these matters. In 2020, a research project was funded to develop a ’data stories tool to support people working and studying in higher education, particularly learning technologists, to develop anonymous speculative stories about what the future of surveillance in higher education might look like, and to draw out themes, concerns about and hopes for that future. The methodology used to design this tool drew from speculative and co-design approaches. This paper discusses how these approaches were mobilised to produce a space for people to make new meanings around surveillance, and to share these with others in a networked environment, in the form of Participatory Speculative Fictions. It discusses a few of the stories produced, and how they shed light on the potential of speculative methods for working with and possibly reconfiguring networked learning futures.